QUALITY OF LIFE AND SELF-CARE IN THE PREVENTION OF DIABETIC FOOT IN PEOPLE WITH DIABETES MELLITUS - Ramirez, Melanne Arantxa Bacilio; Escobar, Lorena Alvarado; Mendoza, Javier Salazar; Santiago, María de los Ángeles Onofre; Montesinos, María Guadalupe Hernández; Escobar, Brianda Alvarado; Contreras, Edith Castellanos; Esparza, Yuzani Pérez (Veredas do Direito, 2026)
Introduction: Diabetes is a public health problem; its complications significantly impact the quality of life of those affected. Diabetic foot (DF) is a leading cause of disability, amputation, and death in people with diabetes, representing one of the most alarming, yet preventable, complications. Objective: To determine the relationship between quality of life (QOL) and the level of self-care in diabetic foot prevention (NAPPD) in people with diabetes mellitus (DM). Method: This was a non-experimental, quantitative, correlational, and descriptive prospective cross-sectional study. It employed the Diabetes Mellitus Quality of Life Questionnaire (EsDQOL), Cronbach's alpha 0.91, and the Self-Care Level Questionnaire for Diabetic Foot Prevention (NAPPD.V2.), Cronbach's alpha 0.94. A non-probability convenience sample of 72 individuals with type 2 diabetes mellitus (DM2) without diabetic foot complications was drawn from a neighborhood in Córdoba, Veracruz. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 21.0, employing descriptive and inferential statistics. Results: Grade I and II obesity was observed in 20.8% of participants, and high body fat content in 68.1%. 100% of participants had a high level of quality of life (QoL); regarding the National Assessment of Pre-Pain Prevention (NAPPD), 94.4% of the sample maintained a medium level. Conclusion: The correlation found suggests that nursing care should focus on health education with the promotion of self-care practices.